The Fiscal Paradox and the Performance of Irrigation Infrastructure: A National Analysis of the Relationship Between Operational and Maintenance Funding and the Sustainability of Local Irrigation Assets - Rahmawati, Irma (Jurnal Indonesia Sosial Sains, 2026)
Irrigation operation and maintenance (OP) management is a key factor in the sustainability of water resource infrastructure services and national food security. In Indonesia, the gap between actual maintenance needs and regional budgeting capabilities remains a major issue. This study analyzes the relationship between regional fiscal capacity, the fulfillment of the Actual Operation and Maintenance Needs (AKNOP), and the achievement of the Irrigation System Performance Index (IKSI) in irrigation areas under regional authority during the 2023–2025 period. Using a mixed-methods approach, the study combines quantitative analysis of national data with a literature review, a survey of OPD perceptions, and practitioner assessments. The results show that high fiscal capacity does not always correlate with irrigation system performance; some regions with large budgets still have low IKSI, while regions with limited budgets are able to maintain services by utilizing the remaining life of the infrastructure. This phenomenon reflects a fiscal paradox, where the problem is more about governance weaknesses than budget limitations. Using the Risk Quadrant Matrix, the study identifies four typologies of irrigation management: acute crisis, governance inefficiency, latent risk, and sustainable zones. The weak integration of AKNOP technical data with the regional budgeting system has created information asymmetry between technical and fiscal units. Recommendations include digital integration of e-AKNOP with the Regional Government Information System (SIPD), strengthening mandatory spending based on infrastructure risk, and revitalizing irrigation OP institutions. These reforms are expected to drive the transformation of irrigation management from a construction-oriented paradigm to an asset-management one.